Principals of diagnostics, treatment and prevention of the diseases of the blood and blood-forming organs - Syvolap, V. D.; Kyselov, S. M.; Nazarenko, E. V.; Bondarenko, A. P.; Сиволап, Віктор Денисович; Кисельов, Сергій Михайлович; Назаренко, Олена Валеріївна; Бондаренко, Олексій Павлович (ЗДМУ, 2015)
This textbook content methods of educational process organization by Module 1, Content Module 4 ―Principals of diagnostics, treatment and prophylaxis of the blood disorders‖ according to demands of Program of Educational Discipline ―Internal Medicine‖. In the textbook there are methodical guidelines for practical lessons and student‘s individual work, clinical protocols of medical help for patients with diseases of the blood and blood-forming organs and tests for evaluation of students‘ initial knowledge level.